2017
DOI: 10.1038/s41598-017-10452-5
|View full text |Cite
|
Sign up to set email alerts
|

Shape-based separation of microalga Euglena gracilis using inertial microfluidics

Abstract: Euglena gracilis (E. gracilis) has been proposed as one of the most attractive microalgae species for biodiesel and biomass production, which exhibits a number of shapes, such as spherical, spindle-shaped, and elongated. Shape is an important biomarker for E. gracilis, serving as an indicator of biological clock status, photosynthetic and respiratory capacity, cell-cycle phase, and environmental condition. The ability to prepare E. gracilis of uniform shape at high purities has significant implications for var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 40 publications
0
92
0
Order By: Relevance
“…Interest in this phenomenon has increased recently with applications in microfluidic devices [3] due to the lack of external forces necessary to induce particle motion transverse to ambient flow. For example, inertial lift has been exploited to selectively separate blood cells [4], cancer cells [5], E. coli [6], and biodiesel-producing algae [7].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in this phenomenon has increased recently with applications in microfluidic devices [3] due to the lack of external forces necessary to induce particle motion transverse to ambient flow. For example, inertial lift has been exploited to selectively separate blood cells [4], cancer cells [5], E. coli [6], and biodiesel-producing algae [7].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to shape-based separation of candida cells using our device, it was confirmed that separation efficiency is affected by asymmetry due to the shape of the formed germ tube. In other studies, the device enables the separation of cells based on shape differences without curvature, which can be a useful biomarker indicating cell type, cell cycle, and differences based on environmental conditions (e.g., fungal pathogens, microalgae, and rod-shaped bacteria (e.g., bacilli)) [34,46,47,68]. In addition, additional numerical analyses and simulations are required to calculate the elastic force exerted on nonspherical particles/cells and to predict the flow characteristics of those in the viscoelastic fluid.…”
Section: Resultsmentioning
confidence: 99%
“…However, most current microfluidic-based techniques use size-based particle/cell separation, although shape can also be a critical biomarker of cell type and cell cycle [27][28][29][30][31]. A few microfluidic techniques have been used for shape-based separation, implementing dielectrophoresis [31], hydrodynamic filtration [32], deterministic lateral displacement [33], and inertial microfluidics [34]. However, dielectrophoresis requires an external setup and conductivity control over the cell medium, and the hydrodynamic filtration technique is limited by low throughput (~15 µL/min).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… achieved a high‐throughput inertial sorting of spheroid particles with different aspect ratios as well as yeast cells at different cell cycle stages in a straight rectangular microchannel. A similar method was later used by the same group to separate microalga Euglena gracilis . Recently, Lu et al.…”
Section: Introductionmentioning
confidence: 99%